Editorial - Manjeet Singh Nain, (Indian Journal of Extension Education, 2023)
EditorialAt the New Delhi G20 summit, G20 leaders vowed to boost global food security and nutrition through research cooperation on resilient grains, also pledged to invest in agriculture to enhance productivity, reduce food waste, and build sustainable, climate-resilient food system, whereas, severe rain battered parts of Turkey, Brazil, Spain, China, and the United States, disrupting local services and creating barriers to accessing food and clean water. Rice prices reached a 15-year high in August, 2023 due to India's ban on overseas sales of non-basmati rice. In between IFFPRI organized second seminar of the CGIAR Policy Seminar Series on Strengthening Food Systems to explore how such schemes could be taken forward in order to help build greater resilience within food systems. There seems a potential solution in regenerative agriculture and to empower eaters through access, affordability and healthy choices, although, a projected 600 million people will still be undernourished for which, countries need to embrace localized solutions and extension system need to gear up. The current issue (October-December, 2023) contains 33 manuscripts including three research tools, three research notes, and twenty seven full-length research papers from cross-sectional authors and content. the measuring tools include; organic poultry farming knowledge test among tribal, gender disparity index in tea gardens  and household food and nutritional security index. The manuscripts on farmers' challenges in adopting soil health card, awareness and determinants of farmers participation in e-marketing and determinants for adopting ICTs by livestock farmers made the ‘research note’ section. The  perception of  participatory management behaviour, evidences of empowering women in aquaculture, measuring kvk-led fisheries extension efforts,  cost and return analysis, indicators for assessing research-extension-farmers linkage in fisheries , knowledge level of maize growers, hybrid rice growers and good management practices in litchi, contribution of women in scientific publications, trends in area production and productivity, assessment of livelihood security and factors effecting food security, effectiveness of video and training on different aspects, use of kinesthetic learning activity, study of operation greens, aspirations of students, e readiness assessment of the NARS, factors of fish purchase, adoption pattern of farm machinery, study on  ZBNF and ARYA programme, Gender Differences in Attitude of University Students towards Gender Roles were covered in ‘Research Article’ section. As usual, the data is regularly being fed to international indexing agencies leading to the indexing of the Indian Journal of Extension Education at various platforms. Now the journal is a legally registered copyrighted material in favour of the Indian Society of Extension Education, New Delhi.I extend sincere thanks to all the expert members of the editorial board for their painstaking efforts. The reviewing contributions of not only the editorial team members but many willful contributors are sincerely acknowledged. I extend my sincere thanks to all the authors for making valuable contributions. The support extended by Executive Council is duly acknowledged. The editorial team also congratulates the President ISEE and whole of the executive team as well as the organizers for successful organizing the ISEE National Seminar-2023 at UAS, Bangalore.Special thanks are extended to the President, ISEE; Dr. U.S. Gautam, Secretary ISEE; Dr. Rashmi Singh, Treasurer, ISEE; Dr. B. K. Singh and Joint Secretary, ISEE; Dr. J. S. Malik for providing insightful thoughts and guidance in bringing out this issue. Dr. Bhanu P. Mishra, Vice President (Central Zone) deserves special thanks for making committed efforts at all stages of ISEE matters.  (Manjeet Singh Nain)